2015
DOI: 10.1259/dmfr.20140126
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging to differentiate metastatic from non-metastatic retropharyngeal lymph nodes in nasopharyngeal carcinoma

et al.

Abstract: Objectives: To evaluate the diagnostic value of diffusion-weighted MRI for differentiating metastatic from non-metastatic retropharyngeal lymph nodes (RLNs) in patients with nasopharyngeal carcinoma (NPC). Methods: Untreated patients with NPC (n 5 145) were scanned with both morphological MRI and diffusion-weighted imaging (DWI). RLNs (n 5 335) were classified as metastatic on the basis of response to therapy as assessed on follow-up MRI. Morphological (short-and long-axial diameters) and functional [mean appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
3
19
2
Order By: Relevance
“…ADC is a quantitative parameter that can indirectly indicate microvascular circulation, cell membrane integrity, and cell density. It has a high sensitivity and specificity in the diagnosis and staging of tumours (17,18). In the present study, The ADCs of primary tumours were significantly lower than those of muscle.…”
Section: Discussionsupporting
confidence: 43%
“…ADC is a quantitative parameter that can indirectly indicate microvascular circulation, cell membrane integrity, and cell density. It has a high sensitivity and specificity in the diagnosis and staging of tumours (17,18). In the present study, The ADCs of primary tumours were significantly lower than those of muscle.…”
Section: Discussionsupporting
confidence: 43%
“…Our study had revealed that mean ADC values in metastatic node (n = 10) {range (0.530-0.815) × 10 −3 s/mm 2 } mean 0.691 × 10 −3 s/mm 2 were significantly lower than that of benign nodes (n = 14){range (1.86-2.45) × 10 −3 s/mm 2 } mean 2.11 × 10 −3 s/mm 2 . Li et al [21] had shown that the mean ADC between metastatic and non-metastatic retropharyngeal nodes were statistically significant differences by DWI (P < 0.001). Holzapfel et al [22] had also demonstrated that mean ADC values (× 10 −3 s/mm 2 ) of benign cervical lymph nodes (1.24 ± 0.16) were significantly higher than that of metastatic lymph nodes (0.78 ± 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased D and f values, an increase in ADC value in the metastatic lymph nodes we attributed to increased molecular water diffusion and perfusion. Furthermore, it has been speculated that necrotic area in the nodes may also affect the ADC values . However, because of the limited spatial resolution of IVIM images, it was very difficult to exclude the micronecrosis from the ROI .…”
Section: Discussionmentioning
confidence: 99%